2015
DOI: 10.1002/ange.201505517
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectricity Generation and Electron–Magnon Scattering in a Natural Chalcopyrite Mineral from a Deep‐Sea Hydrothermal Vent

Abstract: Current high-performance thermoelectric materials require elaborate doping and synthesis procedures,particularly in regardtothe artificial structure,and the underlying thermoelectric mechanisms are still poorly understood. Here,w e report that an atural chalcopyrite mineral, Cu 1+x Fe 1Àx S 2 , obtained from ad eep-sea hydrothermal vent can directly generate thermoelectricity.T he resistivity displayed an excellent semiconducting character,a nd al arge thermoelectric power and high power factor were found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…0.8 W m -1 K -1 ) thermal conductivity of Cu 5.04 Fe 0.9 S 4 is attributed to the presence of appreciable amounts of a chalcopyrite impurity, for which the thermal conductivity is in excess of 6 W m -1 K -1 . Although chalcopyrite has a reasonably high power factor at relatively low temperatures, 13 we have found that samples with high levels of chalcopyrite impurities have significantly higher thermal conductivities, and hence the best thermoelectric performances are always found for samples within the single-phase regions, as determined by powder X-ray diffraction. Table 2).…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 77%
See 1 more Smart Citation
“…0.8 W m -1 K -1 ) thermal conductivity of Cu 5.04 Fe 0.9 S 4 is attributed to the presence of appreciable amounts of a chalcopyrite impurity, for which the thermal conductivity is in excess of 6 W m -1 K -1 . Although chalcopyrite has a reasonably high power factor at relatively low temperatures, 13 we have found that samples with high levels of chalcopyrite impurities have significantly higher thermal conductivities, and hence the best thermoelectric performances are always found for samples within the single-phase regions, as determined by powder X-ray diffraction. Table 2).…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 77%
“…Much of the recent research effort has focused on chalcogenides and there has been a growing realisation that mineral-type phases offer considerable potential as earthabundant thermoelectrics. [9][10][11][12][13][14][15] For example, tetrahedrites have been shown to be promising p-type materials, reaching maximum figures of merit, ZT > 1, at elevated temperatures. 16,17 Similarly, work by Snyder et.…”
Section: Introductionmentioning
confidence: 99%
“…to scatter more phonon, and exploring new unique structures with intrinsically low κ l , which contain strong lattice anharmonicity, low sound velocity, or liquid‐like ions. [ 18–22 ] On the other side, previously effective strategies and concepts have been proposed to improve the power factor, such as modulation doping, [ 23,24 ] magnetic enhancement, [ 25–27 ] band engineering, [ 28–32 ] energy filtering effect, [ 33–36 ] etc. However, it is worth to mention that a realization of the high ZT strongly rely on achieving optimized carrier concentration despite using the strategies above.…”
Section: Introductionmentioning
confidence: 99%
“…For the emergence of life in alkaline hydrothermal vents, such as those in Lost City Hydrothermal Fields, some authors have proposed an analogy with the modern biological electrochemical-driven mechanism, though replacing complex enzyme machinery with inorganic structures. These catalytic converters of free energy are driven by pH, electrochemical and thermal gradients, and are mainly based on mineral catalysts in hydrothermal vents environments (Nakamura et al, 2010;Ang et al, 2015).…”
Section: Geochemical Analysis and Metagenomics Have Shown That Candidmentioning
confidence: 99%
“…and driven by pH, electrochemical gradients between the hydrothermal fluid and early ocean Ang et al, 2015;Yamamoto et al, 2017;Barge et al, 2018;Ooka et al, 2019). Thus, this could be a requisite for the emergence of life in Hadean Earth.…”
Section: Introductionmentioning
confidence: 99%